สภาพปัจจุบัน สภาพที่พึงประสงค์ ความต้องการจำเป็นในการพัฒนาภาวะผู้นำการเปลี่ยนแปลง - Hanrintr , Chanwit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The objectives of this research were 1) to investigate the current conditions, and desirable conditions of transformational leadership of departmental administrators in Nakhon Phanom University, and 2) to examine the needs and necessities for developing departmental administrators’ transformational leadership in Nakhon Phanom University, with a population of 44 departmental administrators. The tool for data collection was a set of 5-level rating scale questionnaires with the discriminative power from .39 to .87, and the reliability of 0.95. The statistics for data analysis were percentage, mean, standard deviation, and Priority Need of Index. The findings were as follows: 1. The current and desirable conditions of departmental administrators’ transformational leadership were overall at a high level. As for the overall desirable conditions, it was at a high level. When considering each aspect, individual aspects were at a high level in all aspects. The desirable conditions were also at a high level in all aspects. 2. The needs for developing departmental administrators’ transformational leadership were organized in descending order of the needs index, namely inspiration, individualized consideration, intellectual stimulation, being a good role model, and having visions, respectively.